Determinants of Mental Health Status in Indonesian Pre-elderly and Elderly with Comorbidities during COVID-19 - Rahman, Beny Aji Ifaudi; Hasanatuludhhiyah, Nurina; Atika; Brihastami Sawitri; Erikavitri Yulianti; Anastasia K. Sikora (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: The pre-elderly and elderly populations with comorbidities are among the vulnerable groups to having mental health issues during COVID-19. This study aimed to examine the mental health status of this population in Indonesia and analyze the associated factors. Methods: This cross-sectional study enrolled 105 pre-elderly and older adults residing in Java Island, Indonesia, in September–October 2021. Mental health status was measured using the Depression, Anxiety, and Stress Scale-21 (DASS-21). Sociodemographic factors, hospital visits, and medication during the pandemic were also asked. Comparison of DASS-21 scores across these factors was analyzed with the Mann-Whitney U test. Results: More than half of the respondents were within a normal range of DASS scores. About 14% of respondents reported depression, and 17% reported stress symptoms, while about 41% were experiencing anxiety. There were gender differences in anxiety and stress scores and education differences in depression. DASS-21 scores were also varied by marital status (p < .05). No significant between-group differences in mental health status according to routine hospital visits and medication during the COVID-19 pandemic. Conclusion: Comorbidities are a risk factor for mental health problems in the pre-elderly and elderly. Women, low economic level, and unmarried individuals were among the vulnerable groups to develop mental health issues during the COVID-19 outbreak.